ON T-HOLLOW-LIFITING MODULES - Yaseen, Sahira M.; Elewi, Alaa A. (Iraqi Journal of Science, 2019)
Let be an R-module, and let be a submodule of . A submodule is called -Small submodule () if for every submodule of such that implies that . In our work we give the definition of -coclosed submodule and -hollow-lifiting modules with many properties.